PENGENALAN POLA TEKSTUR BRODATZ DENGAN METODE JARAK EUCLIDEAN - ZA’IMATUN NISWATI (LPPM, 2012)
This research has a purpose to create a program aids Brodatz texture recognition using Euclidean distance-based Matlab so by inserting a new object (image texture pattern that had never stored in the file), it can be determined that the texture pattern similar to the pattern of the test texture. Euclidean Distance can be used in a statistical approach for texture feature extraction, to calculate the value of contrast, homogeneity, entropy, energy and the correlation. Matlab is a programming application that has been known for manufacturing applications supporting research. Matlab is a programming application in digital image processing that provides a variety of tools that will shorten the time of writing the program so that researchers focus more on results and innovation research. The result is the use of Euclidean Distance for texture pattern recognition is quite good and depending on the color intensity values, on average, entropy, energy, and homogeneity. Kata kunci : texture recognition, Euclidean Distance, Brodatz texture, Matlab